Implementasi Edukasi Preventif dan Pengendalian Kelainan Postur Pada Kelompok Remaja - Aulia Rachman; Ermeisi Er Unja; Akhmad Ridhani; Rizky Ridhayanti; Utomo Wicaksono (JURNAL SUAKA INSAN MENGABDI (JSIM), 2025)
This community service program aimed to improve early detection of scoliosis and enhance postural awareness among students through systematic screening, health education, and follow-up recommendations. The activity was conducted using simple yet reliable scoliosis screening methods, accompanied by brief interviews regarding students’ ergonomic habits and the provision of clear, age-appropriate educational materials for both students and teachers. The results indicated that the program successfully achieved its target number of participants and generated initial data on potential postural deviations among the students. Furthermore, participants demonstrated increased understanding of scoliosis prevention and the importance of maintaining proper body posture during daily activities. This program contributed to promotive and preventive health efforts within the school environment and provided a foundation for ongoing postural monitoring initiatives. Collaboration between schools and health or educational institutions is recommended to develop more comprehensive follow-up programs.